â€œThe Effect of NET PROFIT MARGIN (NPM), RETURN ON ASSETS (ROA), and EARNING PER SHARE (EPS) on stock prices on real estate and property companies listed on IDX period 2011-2013â€ - Putranto, Lucky (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study was to examine the effect of Return on Assets (ROA), Net Profit Margin (NPM) and Earning Per Share (EPS) of the company's price in the Real Estate and Property IDX outstanding in the period 2011 to 2013, the Company's real estate and property considered attractive because many assume that this promising sector for investors This research using secondary data. This study was conducted with a purposive sampling method. To obtain a representative sample in accordance with predetermined criteria. The number of samples obtained are 10 real estate and property companies listed on the Indonesian stock exchange during the period of 2011 through 2013 Data analysis used is multiple linear regression analysis to test the classical assumption of normality test, multicollinearity test, test heterocedasticity, and the autocorrelation test. While hypothesis testing was performed using the F test and T testRegression analysis showed that the Net Profit Margin (NPM) and a significant negative effect on stock prices of real estate and property, Earning Per Share (EPS) and a significant positive effect on stock prices of real estate and property while Return on Assets (ROA) and the positive effect no significant effect on stock prices of real estate and property. Reviews These results explain the donation or contribution of the independent variables (NPM, ROA, and EPS) are included in the regression equation to price, is equal to 66.5%, while 33.5% was Contributed by other variables not included in this equation.Keywords: Stock Prices, Real Estate and Property, Return On Assets (ROA), Net Profit Margin (NPM), Earning Per Share (EPS)